FREE-FLOW SPEED ON TWO-LANE RURAL HIGHWAYS: AN EMPIRICAL EVALUATION OF ESTIMATION MODELS (Malaysian Journal of Civil Engineering, 2018)
Free-flow speed (FFS); a fundamental parameter in the analysis of two-lane highways, is either estimated through direct field measurement or using analytical model. Regarding the latter approach, the Malaysian Highway Capacity Manual (MHCM) established a model for estimating FFS based on base-free-flow speed (BFFS), roadway’s geometric features and proportion of motorcycles in the traffic stream. Likewise, the Highway Capacity Manual (HCM) suggested an approach for direct field measurement of FFS; preferably, at a combined two-way flow rate not in excess of 200 veh/h. For most two-lane highways, observing a two-way flow rate of 200 veh/h or less is rarely possible. In such a case, the HCM recommended that mean speed could be observed at flow rates higher than the limiting value and adjusted accordingly based on an analytical model provided by the manual. This paper presents an empirical appraisal of the MHCM and HCM – FFS estimation models. Data for the study were collected from four directional segments of rural two-lane highways in Johor, Malaysia. A video recording intrumented test vehicle was used for observing the relevant variables needed in this study. An analysis of the obaseved data resulted in mean FFS values of 83.35 km/h and 83.03 km/h from HCM and MHCM models, respectively. FFS estimates from the two data sets were compared to ascertain the degree of their consistency or otherwise using statistical analysis. Results from statistical analysis using t-statistic at 0.05 significance level indicates that there is no statistically significant difference between the FFS estimates from the two approaches. Thus, finding from this study suggests that either of the two approaches could be used for measuring FFS; particularly, at combined two-way flow rates exceeding 200 veh/h.